2016
DOI: 10.13005/ojc/320163
|View full text |Cite
|
Sign up to set email alerts
|

Application of Response Surface Methodology to Modeling and Optimization of Removal of Bismarck Brown and Thymol Blue by Mn-Fe2O4- NPs-AC: (Kinetics and Thermodynamic Studies)

Abstract: The focus of this research is on the rapid ultrasound-assisted removal of Bismarck Brown (BB) and Thymol Blue(TB) dyes from aqueous solutions using Mn-Fe 2 O 4 nanoparticles loaded on activated carbon (Mn-Fe 2 O 4 -NPs-AC) as a low cost and environmental friendly adsorbent. The adsorbent was characterized by SEM, FTIR and XRD. The effect of variables such as initial concentration of BB, initial concentration of TB, pH of the solution, adsorbent dosage and sonication time on the removal percentages of BB and TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The performance of the proposed method has been compared with other adsorbents (Table 5). The adsorption capacity and contact time for present work are superior for other adsorbents BB and TB removal [41][42][43]. The results indicated that the ultrasound-assisted removal method has good ability to improve the efficiency of dyes removal.…”
Section: Comparison Of Various Adsorbentmentioning
confidence: 70%
“…The performance of the proposed method has been compared with other adsorbents (Table 5). The adsorption capacity and contact time for present work are superior for other adsorbents BB and TB removal [41][42][43]. The results indicated that the ultrasound-assisted removal method has good ability to improve the efficiency of dyes removal.…”
Section: Comparison Of Various Adsorbentmentioning
confidence: 70%
“…Disulfine blue (DSB, Fig. 1(b) is a hazardous dye that is widely used for dyeing of wool and silk, carbon paper, cosmetics, and leather 9,10 . …”
Section: Introductionmentioning
confidence: 99%